2011
DOI: 10.1002/crq.20043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neutral, evaluative, and pressing mediator strategies

Abstract: This study investigates the effects of three mediator strategies-neutral, evaluative, and pressing-upon agreement and satisfaction in 100 civil case mediations. The authors found a significant difference in that a neutral strategy resulted in agreement only 28 percent of the time, whereas the evaluative strategy had an agreement rate of 69 percent and the pressing strategy a 57 percent rate. They also found that consistent use of each strategy throughout the mediation increased the agreement rate. When produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The literature regarding directive or evaluative mediator strategies is mixed (American Bar Association Section of Dispute Resolution, 2017). In an observation study of general civil mediation, pressing and evaluative mediator behaviors increased settlement, but modestly reduced disputant satisfaction (Wall et al, 2011). In an observation study of community mediation, directive mediator behaviors (making suggestions, expressing opinions, telling participants how to behave, and advocating for a particular outcome) were negatively associated with participants reporting that they could express themselves, that the mediator understood what they were expressing, and that they were satisfied with the mediation process (Charkoudian & Wayne, 2010).…”
Section: Directive or Evaluative Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature regarding directive or evaluative mediator strategies is mixed (American Bar Association Section of Dispute Resolution, 2017). In an observation study of general civil mediation, pressing and evaluative mediator behaviors increased settlement, but modestly reduced disputant satisfaction (Wall et al, 2011). In an observation study of community mediation, directive mediator behaviors (making suggestions, expressing opinions, telling participants how to behave, and advocating for a particular outcome) were negatively associated with participants reporting that they could express themselves, that the mediator understood what they were expressing, and that they were satisfied with the mediation process (Charkoudian & Wayne, 2010).…”
Section: Directive or Evaluative Strategiesmentioning
confidence: 99%
“…In an observation study of general civil mediation, pressing and evaluative mediator behaviors increased settlement, but modestly reduced disputant satisfaction (Wall et al, 2011). In an observation study of general civil mediation, pressing and evaluative mediator behaviors increased settlement, but modestly reduced disputant satisfaction (Wall et al, 2011).…”
Section: Directive or Evaluative Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e eff ectiveness of a mediator may be aff ected by his or her choice of mediation strategy. A number of studies established that the pressing strategy of mediators more often leads to agreements than the neutral strategy does (Bercovitch and Houston 1993;De Dreu and Carnevale 2003;Kressel and Pruitt 1989;Wall, Dunne, and Chan-Serafi n 2011). Bercovitch and Houston (1993) suggested that pressing and directive strategies help parties equalize power imbalances and generally move the disputants toward a more cooperative attitude toward one another.…”
Section: Eff Ectiveness Of a Mediator's Intervention In Solving Intermentioning
confidence: 99%
“…The effectiveness of a mediator may be affected by his or her choice of mediation strategy. A number of studies established that the pressing strategy of mediators more often leads to agreements than the neutral strategy does (Bercovitch and Houston ; De Dreu and Carnevale ; Kressel and Pruitt ; Wall, Dunne, and Chan‐Serafin ).…”
Section: Introductionmentioning
confidence: 99%